AKULTURASI ARSITEKTUR TRADISIONAL DAN MODERN PADA BANGUNAN KLENTENG SATYA BUDHI DI BANDUNG - Hendra Hartarto Sugianto; Bachtiar Fauzy (Riset Arsitektur (RISA), 2022)
Abstract – Indonesia is a unitary state that has various ethnicities and cultures. Klenteng is a worship buildings for minority communities because there are not too many of them and are scattered in various regions in Indonesia. Klenteng uses the concept of architectural acculturation that combines traditional and modern elements that are widely applied, one of which is the Satya Budhi Klenteng in Bandung City. In the design method, the building must apply traditional elements because it is an effort to preserve or maintain this culture in today's times. In the case study, the Satya Budhi Klenteng will describe the traditional and modern elements based on the concept of site, mass structure, spatial arrangement, construction structure and ornamentation. After that, you will get the dominating aspect between traditional and modern elements based on the main part of the building. The results of the process will show dominance in applying traditional and modern elements to the Satya Budhi Klenteng. This research uses descriptive methods that describe case studies, analytical methods that analyze case studies based on theory and interpretative methods in producing conclusions which are an attempt to understand the dominance between traditional and modern elements based on the design method. As well as, to define the concept of acculturation architecture used through the design of worship buildings. Keywords: architectural acculturation, traditional architecture, modern architecture, Satya Budhi Klenteng